Attenuation of cGAS‐STING signaling is mediated by a p62/SQSTM1‐dependent autophagy pathway activated by TBK1. (1st March 2018) - Prabakaran, Thaneas; Bodda, Chiranjeevi; Krapp, Christian; Zhang, Bao‐cun; Christensen, Maria H; Sun, Chenglong; Reinert, Line; Cai, Yujia; Jensen, Søren B; Skouboe, Morten K; Nyengaard, Jens R; Thompson, Craig B; et al.
Abstract: Negative regulation of immune pathways is essential to achieve resolution of immune responses and to avoid excess inflammation. DNA stimulates type I IFN expression through the DNA sensor cGAS, the second messenger cGAMP, and the adaptor molecule STING. Here, we report that STING degradation following activation of the pathway occurs through autophagy and is mediated by p62/SQSTM1, which is phosphorylated by TBK1 to direct ubiquitinated STING to autophagosomes. Degradation of STING was impaired in p62‐deficient cells, which responded with elevated IFN production to foreign DNA and DNA pathogens. In the absence of p62, STING failed to traffic to autophagy‐associated vesicles. Thus, DNA sensing induces the cGAS‐STING pathway to activate TBK1, which phosphorylates IRF3 to induce IFN expression, but also phosphorylates p62 to stimulate STING degradation and attenuation of the response. Synopsis: Stimulation of the cGAS‐STING pathway by cytosolic DNA leads to STING ubiquitination and degradation. The downstream cGAS‐STING kinase TBK1 also phosphorylates the selective autophagy receptor p62, which in turn directs STING for degradation by autophagy. Abrogation of autophagy severely impaired DNA‐stimulated STING degradation. p62 is essential for DNA‐stimulated STING degradation. Cells lacking p62 have elevated interferon responses to cytoplasmic DNA and DNA pathogens. TBK1 phosphorylates p62, which promoted STING degradation and regulation of the pathway. Abstract : Stimulation of the cGAS‐STING innate immunity pathway by cytosolic DNA leads to TBK1‐mediated phosphorylation of the selective autophagy receptor p62, directing ubiquitinated STING to autophagosomes and degradation.